1996
DOI: 10.1128/aac.40.6.1486
|View full text |Cite
|
Sign up to set email alerts
|

Use of PCR and culture to detect Helicobacter pylori in naturally infected cats following triple antimicrobial therapy

Abstract: Helicobacter pylori causes gastritis and peptic ulcers and is linked to gastric cancer. Domestic cats from a commercial source were found to be naturally infected with H. pylori, and studies were undertaken to eradicate H. pylori from infected cats by using triple antimicrobial therapy. Eight cats infected with H. pylori were used in the study. Six cats received a 21-day course of oral amoxicillin, metronidazole, and omeprazole, and two cats served as controls. Two weeks and 4 weeks posttreatment (p.t.), all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 39 publications
0
26
2
2
Order By: Relevance
“…In an animal model, Cellini et al (1994) demonstrated that up to 3 months after inoculation viable but not culturable forms of H. pylori could still be detected in the mouse stomach [28]. A few studies [29, 30] were carried out to evaluate triple therapy comparing PCR with culture. However no report has included nested PCR.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model, Cellini et al (1994) demonstrated that up to 3 months after inoculation viable but not culturable forms of H. pylori could still be detected in the mouse stomach [28]. A few studies [29, 30] were carried out to evaluate triple therapy comparing PCR with culture. However no report has included nested PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Perkins et al observaron, en gatos infectados de forma natural por H. pylori, que 6 semanas después del tratamiento de erradicación, el análisis del jugo gástrico era positivo para H. pylori en un solo gato, pero mediante la reacción en cadena de la polimerasa se identificó la presencia de material genético de H. pylori en todos los gatos tratados. Las lesiones histológicas eran compatibles con gastritis crónica con la presencia de folículos linfoides, aunque los bacilos de H. pylori fueron detectados en un solo gato 48 .…”
Section: Susceptibilidad De La Forma Cocoide a Los Antibióticosunclassified
“…Helicobacter felis is a naturally occurring pathogen in cats that appears to be prevalent in some colonies, but its prevalence or significance as an agent of clinical diseases in the general cat population is not clear (Lee et al, 1988;Perkins et al, 1996). Helicobacter felis is a naturally occurring pathogen in cats that appears to be prevalent in some colonies, but its prevalence or significance as an agent of clinical diseases in the general cat population is not clear (Lee et al, 1988;Perkins et al, 1996).…”
Section: Feline Retroviruses: Models Of Human Aids and Potential Viramentioning
confidence: 99%
“…Helicobacter felis is a naturally occurring pathogen in cats that appears to be prevalent in some colonies, but its prevalence or significance as an agent of clinical diseases in the general cat population is not clear (Lee et al, 1988;Perkins et al, 1996). In addition to H. felis infection, cats appear also to be naturally infected with H. pylori, raising the possibility that domestic cats could serve as a reservoir for this human pathogen (Perkins et al, 1996). In addition to H. felis infection, cats appear also to be naturally infected with H. pylori, raising the possibility that domestic cats could serve as a reservoir for this human pathogen (Perkins et al, 1996).…”
Section: Feline Retroviruses: Models Of Human Aids and Potential Viramentioning
confidence: 99%